Pengaruh Penekatan Pembelajaran Drill Dan Bermain Terhadap Hasil Belajar Servis Bawa Dalam Permainan Bola Voli Untuk Siswa Laki-Laki Kelas VIII SMP Negeri 4 Tambang - Mimi Yulianti Mimi; Rices Jatra; M. Ghaza Algazali; Yuda Hadi Purnomo; Leni Apriani; Sujarwo (Jurnal Olahraga Indragiri, 2026)
This study aims to determine the effect of the drill and play learning approach on the learning outcomes of underhand serve in volleyball for eighth-grade male students of SMP Negeri 4 Tambang, Tambang District. This study used an experimental method with a two-group pretest–posttest design. The subjects were eighth-grade male students who were divided into two groups: a group given a drill learning approach and a group given a play learning approach. The research instrument was a volleyball underhand serve skill test that had been tested for validity and reliability. Data were analyzed using descriptive and inferential statistical tests, including normality tests, homogeneity tests, and hypothesis testing using the t-test. The results showed that there was a significant effect of the drill and play learning approach on the learning outcomes of underhand serve in volleyball. The drill learning approach provided a higher increase in learning outcomes compared to the play learning approach. Thus, it can be concluded that the drill learning approach is more effective in improving the learning outcomes of underhand serve in volleyball for eighth-grade male students of SMP Negeri 4 Tambang, Tambang District.